Transient left anterior and septal fascicular blocks after self‐expandable percutaneous transcatheter aortic valve implantation. Issue 4 (19th April 2018) - Pérez‐Riera, Andrés R.; Barbosa‐Barros, Raimundo; Cabral de Oliveira, Mariana F.; Daminello‐Raimundo, Rodrigo; de Abreu, Luiz C.; Nikus, Kjell
Abstract : Transcatheter aortic valve implantation (TAVI) is indicated in severe symptomatic aortic stenosis, when there is intermediate‐high surgical risk, or a condition considered inoperable, as in the case of "porcelain aorta" that could turn clamping or cannulation of the ascending aorta hazardous in open‐heart surgery. Among the complications of this less invasive procedure, intraventricular conduction disorders subsequent to the procedure stand out. TAVI causes worsening of intraventricular dromotropic disorders in more than 75% of the cases, with the presence of preexisting right bundle branch block and first‐degree atrioventricular block, deep prosthesis implant, male gender, size of the aortic annulus smaller than the prosthesis, and porcelain aorta being predictive of requirement for permanent pacemaker implant.